2012
DOI: 10.1017/s0024282911000909
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic analysis of the foliose lichen Parmotrema tinctorum using microsatellite markers: association of mycobiont and photobiont, and their reproductive modes

Abstract: To investigate the association between, and the reproductive modes of, mycobiont and photobiont in the lichen Parmotrema tinctorum, microsatellite markers (SSR markers) were developed for both bionts and genotypic analysis was performed for thalli in a Pinus thunbergii forest. In a within-thallus analysis, tissue pieces were sampled from many portions within each of five thalli. Within-thallus variation for both mycobiont and photobiont differed among the thalli investigated, suggesting that a single thallus c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 51 publications
1
44
0
Order By: Relevance
“…We found evidence of recombination at moderate frequencies in all three Lobaria species. Recombination has previously been reported for Letharia gracilis (Kroken & Taylor 2001), Letharia vulpina (Arnerup et al 2004), Ramalina menziesii (Werth & Sork 2008;Werth & Sork 2010), and Parmotrema tinctorum (Mansournia et al 2011). Our study species have a mixed reproductive mode, with the predominance of the clonal component in some and of recombination in others populations, a pattern previously reported for L. pulmonaria .…”
Section: Correlated Reproductive Modes Across Species and Concerted Fmentioning
confidence: 79%
“…We found evidence of recombination at moderate frequencies in all three Lobaria species. Recombination has previously been reported for Letharia gracilis (Kroken & Taylor 2001), Letharia vulpina (Arnerup et al 2004), Ramalina menziesii (Werth & Sork 2008;Werth & Sork 2010), and Parmotrema tinctorum (Mansournia et al 2011). Our study species have a mixed reproductive mode, with the predominance of the clonal component in some and of recombination in others populations, a pattern previously reported for L. pulmonaria .…”
Section: Correlated Reproductive Modes Across Species and Concerted Fmentioning
confidence: 79%
“…Conversely, in the case of the predominantly asexual lichen-forming species Lobaria pulmonaria , SSR-based studies have shown highly clonal and structured populations, resulting from low level of recombination and limited dispersal capacity of vegetative propagules2021. More pronounced population structure seems to be a common trend of vegetatively reproducing lichens as shown in several studies on other systems (e.g., Parmotrema tinctorum 22, Parmelina tiliacea 23). Lobaria pulmonaria is also the only lichen species for which population-level data on the distribution of mating-type idiomorphs is available so far13.…”
mentioning
confidence: 96%
“…Also, initial developmental stages can contain different photobionts than the adult thallus (Friedl 1987). This can result in multiple photobiont or fungal genotypes within a lichen thallus; such intrathalline variability has indeed been reported by several genetic studies (Casano et al 2011;Dal Grande et al 2014a;del Campo et al 2013;Larson and Carey 1986;Mansournia et al 2011;Piercey-Normore 2006a). HTS of lichen samples is likely to provide information on intrathalline diversity of photobionts and mycobionts in a variety of lichen species.…”
Section: Diversity Of Symbiont Associations and Associated Organismsmentioning
confidence: 89%